Describing electronic, digital, and other media using AACR2 and RDA : - Weber, Mary Beth (Neal-Schuman Publishers, 2011)
Authors Mary Beth Weber and Fay Austin provide the best way to insure access to diverse new content will find expert solutions in this vital new resource. Streaming video, Internet sites, dual-disc DVDs, blogs and listservs are just some of the rapidly emerging, and often complicated, new resources covered in this current, easy-to-follow manual. The authors dedicate separate chapters to each non-print and e-resource format, and include corresponding examples to help demonstrate practical implementation of these critical new skills.